Analysis on Crack Mechanism of Passivation Layer in Power Packaging - Zhiwen CHEN; Xingwang HU; Yong LIU; Li LIU; Sheng LIU (机车电传动)
Passivation crack on the surface of power chip seriously affects the reliability of power devices. In this paper, the mechanism of passivation layer failure was explored by temperature cycling test on D-PAK module. Temperature cycling tests showed that the cracks developed in the passivation film over the aluminum film close to the boundary, but were rarely observed in stripe. If the cracks in passivation film remains the same as the first cracks in manufacturing processes, there would be a long service life for the device. This requires that the stress intensity factor is always less than the toughness of passivation film. Otherwise, the crack will grow and propagate in the subsequent cycles. Griffith criterion can be used to know whether cracks will occur or not. Finally, the estimation method of the critical value of crack initiation cycle was provided, and the crack initiation diagram was illustrated as the failure criterion of passivation layer. A method was proposed to predict whether the passivation has ratcheting deformation or crack to improve the reliability of devices.